2009
DOI: 10.1128/jvi.00351-09
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus RTA Promotes Degradation of the Hey1 Repressor Protein through the Ubiquitin Proteasome Pathway

Abstract: The Kaposi's sarcoma-associated herpesvirus (KSHV) replication and transcription activator (RTA) protein regulates the latent-lytic switch by transactivating a variety of KSHV lytic and cellular promoters. RTA is a novel E3 ubiquitin ligase that targets a number of transcriptional repressor proteins for degradation by the ubiquitin proteasome pathway. Herein, we show that RTA interacts with the cellular transcriptional repressor protein Hey1. We demonstrate that Hey1 is a target for RTA-mediated ubiquitination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 69 publications
3
83
0
Order By: Relevance
“…We demonstrated that KSHV infection unregulated the level of expression of endogenous Hey1 in B and 293T cells and LANA takes major responsibility for it. Our results showed that Hey1 was degraded by the ubiquitinproteasome system, as indicated by other research (47,48). Ectopic expression of LANA significantly inhibited the degradation of Hey1, in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…We demonstrated that KSHV infection unregulated the level of expression of endogenous Hey1 in B and 293T cells and LANA takes major responsibility for it. Our results showed that Hey1 was degraded by the ubiquitinproteasome system, as indicated by other research (47,48). Ectopic expression of LANA significantly inhibited the degradation of Hey1, in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…To remove genomic DNA, total RNA was digested with RNase-free DNase I (New England Biolabs) at 37°C for 1 h. DNase I digestion was quenched by heat inactivation at 70°C for 20 min, and total RNA was repurified with TRIzol reagent. cDNA was prepared with 1.5 g total RNA, reverse transcriptase (Invitrogen), and 0.5 g/l primer oligo(dT) [12][13][14][15][16][17][18][19] . RNA was then removed by incubation with RNase H (Epicentre).…”
Section: Methodsmentioning
confidence: 99%
“…Several cellular factors, such as XBP-1, Ras, Ets-1, PARP-1, hKFC, CBP, the SWI/SNF chromatin remodeling complex, the TRAP/Mediator complex, RBP-J, human Notch intracellular domain, and HMGB1, have been shown to promote KSHV reactivation and/or lytic gene expression (11,31,32,44,71,72,75,76), suggesting a close link between many cellular processes and KSHV reactivation. Other cellular factors, such as Oct-2, KAP-1, and Hey1, were found to inhibit KSHV reactivation and/or lytic gene expression (12,19,25). However, the regulation of KSHV reactivation by cellular signals is still not fully understood.…”
mentioning
confidence: 99%